UPAYA MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V DENGAN MODEL PROBLEM BASED LEARNING - Suriana Suriana (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2021)
This research is motivated by the lack of student learning outcomes. The purpose of this study was to find out how efforts can be made to improve student learning outcomes in science subjects through the application of Problem Based Learning (PBL) learning activities in Class VA SDN 57/X Kampung Laut. This research uses categorical action research (CAR). The CAR used is the research participant. The research design leads to the model developed by Kemis and Mc. Taggart is the existence of planning (planning), action (action), observation (observing), and reflection (reflecting) which is tried by means of cycles. The points of this research are VA class students who open 21 people. The results of data analysis are then used for reflection in the next cycle. Information collection equipment used were observations, field notes and questionnaires. Data from observation sheets, field notes, and questionnaires were analyzed qualitatively. The results of this research in the first cycle if 21 students there are 13 students who are successful (61.90%) and those who are not successful as many as 8 people (38.10%), while the second cycle. students there are 16 students who complete (76.20%) and who do not complete as many as 5 people (23.80%), for an average value of 73.57. Then it has fulfilled the percentage of 70%, so it does not need to be carried out to the next cycle.